Pengelolaan Limbah Cair Dan Limbah Padat Di Bandar Udara Ngurah Rai-Bali - Rezki, Yuke Sri; Kusumawati, Dedes (Sekretariat Badan Penelitian dan Pengembangan Perhubungan, 2012)
Assessment of Management of Liquid Waste and Solid Waste useful to prot>ide a11 Ol'erview for stakeholders in making decision to develop a waste management system of output from ai1port operation which sustainable and environmentally friendly. T71e assessme11t took a case study at Ngurah Rai Airport which is the second largest airport in Indonesia. T7re assessment looks at the waste management procedures, both liquid and solid waste at tlie airport. In addition, this study provides arz overview of relationship between the number of passengers, the number of aircraft and the production of solid waste. Given this assessment can be seen that the waste management system has been implemented and can provide recommendations related to the waste management system to other airports.